P.023 Eculizumab shows consistent improvements across muscle groups in patients with AChR antibody-positive refractory myasthenia gravis. (June 2019) - Larue, S; Mantegazza, R; Fujita, KP; O'Brien, F; Howard, JF
Abstract : Background: The physician-reported Quantitative Myasthenia Gravis (QMG) test was a key efficacy measure in REGAIN, a 26-week, phase 3, placebo-controlled study of eculizumab in anti-acetylcholine receptor antibody-positive refractory generalized MG. Ocular and generalized weakness have shown variable responses to therapies including prednisone and intravenous immunoglobulin/plasma exchange. Using the patient-reported MG Activities of Daily Living (MG-ADL) scale during REGAIN, eculizumab showed a consistent trend toward rapid and sustained improvement across bulbar, respiratory, limb and ocular domains. We analyzed the effect of eculizumab on bulbar, respiratory, gross motor and ocular domains during REGAIN, using the QMG test. Methods: QMG domain score changes to REGAIN week 26 were determined for patients with abnormal baseline scores. Repeated-measures analyses were performed for bulbar (swallowing/speech), respiratory (forced vital capacity), gross motor (limb/axial motor items) and ocular (ocular/facial muscles) domains. Results: Eculizumab-treated patients showed improvements in all four QMG domain scores to week 26. Rapid, sustained improvements were demonstrated across all domains, with a trend toward significant differences between eculizumab and placebo (bulbar, p =0.0628; respiratory, p =0.0682; gross motor, p =0.0114; ocular, p =0.0017). The eculizumab safety profile was consistent with previous reports. Conclusions: Eculizumab demonstrated a consistent response across all QMG muscle domains. This aligns with previously reported MG-ADL findings with eculizumab. (NCT01997229).